2014
DOI: 10.1002/jez.1859
|View full text |Cite
|
Sign up to set email alerts
|

Proportional accumulation of yolk proteins derived from multiple vitellogenins is precisely regulated during vitellogenesis in striped bass (Morone saxatilis)

Abstract: We quantified three vitellogenins (VtgAa, VtgAb, VtgC) or their derived yolk proteins (YPs) in the liver, plasma, and ovary during pre-vitellogenic (PreVG), mid-vitellogenic (MVG), and late-vitellogenic (LVG) oocyte growth and during post-vitellogenesis (PostVG) in the striped bass (Morone saxatilis) using label-free quantitative mass spectrometry (MS). Western blotting of the samples using antisera raised against gray mullet (Mugil cephalus) lipovitellins derived from VtgAa, VtgAb, and VtgC confirmed the MS r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 48 publications
9
32
0
Order By: Relevance
“…Samples were measured in triplicate using a 7300 real-time PCR system (Applied Biosystems) and gene expression was reported as copy number calculated from serially diluted plasmid DNA standard curves. Picha and colleagues ( 38,39 ) show that normalization of target RNA to total RNA shows similar results to that for normalization to 18S RNA in hybrid striped bass, and we also show this trend when normalization of target RNA to total RNA is compared with normalization to ribosomal protein L9 in striped bass ( 37 ). Therefore, we used total RNA for normalization of lr8 Ϫ and lrp13 gene expression.…”
Section: Real-time Quantitative Rt-pcrsupporting
confidence: 72%
See 1 more Smart Citation
“…Samples were measured in triplicate using a 7300 real-time PCR system (Applied Biosystems) and gene expression was reported as copy number calculated from serially diluted plasmid DNA standard curves. Picha and colleagues ( 38,39 ) show that normalization of target RNA to total RNA shows similar results to that for normalization to 18S RNA in hybrid striped bass, and we also show this trend when normalization of target RNA to total RNA is compared with normalization to ribosomal protein L9 in striped bass ( 37 ). Therefore, we used total RNA for normalization of lr8 Ϫ and lrp13 gene expression.…”
Section: Real-time Quantitative Rt-pcrsupporting
confidence: 72%
“…For the largest group of fi shes (Acanthomorpha), a system of dual ovarian Vtgrs (Lr8 Ϫ and Lrp13) could explain, in part, the disparate accumulation and hydrolysis of egg yolk derived from the functionally distinct VtgAa and VtgAb, which are critical processes governing acquisition of proper egg buoyancy and provision of different types of nutrients to embryos and larvae ( 37,57,58 ). During maturation, yolk proteins derived from VtgAa are disproportionally hydrolyzed to free amino acids, which osmotically drive oocyte hydration and are nutrients selectively utilized by early embryos.…”
Section: Ligand and Western Blottingmentioning
confidence: 99%
“…All qPCR products were electrophoresed on agarose gels and sequenced to verify that each primer set specifically amplified a single target piscidin. Data was normalized to the starting total RNA concentration as we have previously described [42]. Pooled total RNA samples from hybrid striped bass not used in these experiments were included on each plate to normalize the data between plates.…”
Section: Methodsmentioning
confidence: 99%
“…This is particularly true for Salmonidae. In addition, in fish species where the complete form of Vtg has been further classified into VtgAa and VtgAb, the ratio of subtypes present in the blood depends on each species [117,118]. Because of the large molecular weight differences, the ratio of complete to incomplete forms of Vtg can be readily determined by electrophoresis and similar methods.…”
Section: Applications Of Vitellogenin As Biomarkers For Detection Of mentioning
confidence: 99%
“…Our recent research on the physiological functions of each type of Vtg during oocyte maturation and embryogenesis following fertilization suggested that egg quality is directly dependent on the relative abundance (accumulation ratio) of each Vtg within the ovulated eggs [117,118]. Assuming that this hypothesis is correct, when EEDCs disrupt the ratios of different forms of Vtgs found in the blood or accumulated in the egg, this suggests a potential direct impact on fertilization or survival rates.…”
Section: Interpretation Of Vitellogenin Inductionmentioning
confidence: 99%